Gambogic acid suppresses hypoxia‐induced hypoxia‐inducible factor‐1α/vascular endothelial growth factor expression via inhibiting phosphatidylinositol 3‐kinase/Akt/mammalian target protein of rapamycin pathway in multiple myeloma cells. Issue 8 (27th July 2014) - Wang, Fei; Zhang, Wei; Guo, Liting; Bao, Wen; Jin, Nan; Liu, Ran; Liu, Ping; Wang, Yonghui; Guo, Qinglong; Chen, Baoan
<x xml:space="preserve">Abstract</x> In multiple myeloma (MM), the hypoxic environment is an important factor causing tumor angiogenesis, which is strongly correlated to disease progression and unfavorable outcome by activating the key transcription factor, hypoxia‐inducible factor‐1α (HIF‐1α). Gambogic acid (GA) is the major active ingredient of gamboge, which has been shown to possess antitumor effect by in vitro and in vivo study. However, the underlying molecular mechanism of whether GA inhibits tumor angiogenesis remains poorly understood. In this study, we investigated the effects of GA on expression of HIF‐1α, and its downstream target gene vascular endothelial growth factor (VEGF) in human MM U266 cells. We found that hypoxia induced increase in the level of HIF‐1α subunit protein and activated the phosphatidylinositol 3‐kinase (PI3K)/Akt/mammalian target protein of rapamycin (mTOR) pathway. Moreover, the treatment with GA markedly decreased HIF‐1α and VEGF expression under hypoxic conditions. Mechanistic studies exhibited that GA inhibited the production of HIF‐1α by reducing phosphorylation of Akt and mTOR in U266 cells. Furthermore, in vivo study revealed that intravenous injection of GA once every other day for 2 weeks could suppress tumor volumes by antiangiogenesis activity. Taken together, our results identify that GA suppresses hypoxia‐activated pathways that are linked to MM progression, at least partly, by the inhibition of the PI3K/Akt/mTOR signaling pathway. Therefore, GA may be a new potent therapeutic agent against human MM cells.